Quốc Âm Thi tập - Nguyễn Trãi, 1380-1442. (Huế : Thuận Hoá, 2000)
Sách giới thiệu tác phẩm Quốc Âm thi tập của đại thi hào dân tộc Nguyễn Trãi.
Keywords: Nguyễn Trãi, -- 1380-1442.; Thơ; Nguyễn Trãi; Văn học Việt; Thi ca Việt -- Nguyễn Trãi, -- 1380-1442.; Nguyễn Trãi, -- 1380-1442.